en - Putri, Syahdila Ika; Ambalegin, Ambalegin (e-Journal of Linguistics; Vol 16 No 2 (2022): ejl-JulyDO - 10.24843/e-jl.2022.v16.i02.p10, 2022)
The article raised the implied meaning contained in the film entitled "suspicious couple" by Chiko Chiata. The goals or aims of this research are to uncover the use of implicature in a film using Grice's cooperative principle framework and to entangle the implied meanings in the conversations in terms of their maxim arrangement. The theory used is conversational implicature based on theory (Grice, 1989). Every implied meaning or conversational implicature in it is what is explained. To explain the various implied meanings, it is necessary to use methods and methods that are in accordance with the lines. the methodology used is the type of research, the method of collecting and analyzing data such as qualitative descriptive taken from theory (Sudaryanto, 2015) is this research method because words, phrases are forms to explain data. For data analysis, pragmatic identity is used in this study. Observational and non-participatory methods were applied in data collection. This study finds many implied meanings in both pronunciation and movement in the film "Suspicious Partner" which is a crime and life genre. but in this study took 16 examples of implied meaning to be understood properly. whose discussion is related to the type of conversational implicature in its implicature branch.